Multi-Machine Stability Using Dynamic Inversion Technique - Abha Tripathi; K. Uma Rao; L. Venkatesha (Institute of Advanced Engineering and Science, 2017)
Stability studies of multi machine system are a major concern to power system engineers due to the increasing complexity involved. This paper deals with the application of a nonlinear technique called Dynamic Inversion, to TCSC for the improvement of stability of multi-machine system. The transient stability studies for various cases: without any controller, with 75% line compensation and with Dynamic Inversion technique, are compared. The critical clearing time as well as the maximum loading ability is also discussed. The result for the nonlinear controller is found to be better than all the other cases.